Monocyclic and monoaromatic naphthenic acids: Synthesis and characterisation - Rowland, S.; West, C.; Scarlett, Alan; Jones, D.; Boberek, M.; Pan, L.; Ng, M.; Kwong, L.; Tonkin, A. (2011)
Characterisation of the complex mixtures of carboxylic acids (naphthenic acids) occurring in crude oils and in degraded oil sands is environmentally important. Indeed some acids in waters from oil platforms are apparently hormonally active, and the oil sands acids are said to be toxic to a wide range of biota. Previous attempts to identify monocyclic and monoaromatic naphthenic acids have been hampered by the lack of authenticated synthetic reference compounds. Some studies have indicated that acids with ethanoic acid side chains are present in the naphthenic acids mixtures, so in the present study, we synthesised and characterised by mass spectrometry, a range (C8-14) of monoaromatic and monocyclic ethanoic acids. Using 2-D comprehensive gas chromatography-mass spectrometry, we then compared the retention times and mass spectra of the synthetic acids with those of a commercial naphthenic acids mixture. Some alicyclic and numerous aromatic acids were successfully identified. © 2011 Springer-Verlag.